Genetic Structure and Molecular Variability Analysis of Citrus sudden death-associated virus Isolates from Infected Plants Grown in Brazil - Matsumura, Emilyn Emy [UNESP]; Della Coletta Filho, Helvecio; Dorta, Silvia de Oliveira; Nouri, Shahideh; Machado, Marcos Antonio (Mdpi Ag, 2016)
Citrus sudden death-associated virus (CSDaV) is a monopartite positive-sense single-stranded RNA virus that was suggested to be associated with citrus sudden death (CSD) disease in Brazil. Here, we report the first study of the genetic structure and molecular variability among 31 CSDaV isolates collected from both symptomatic and asymptomatic trees in CSD-affected areas. Analyses of partial nucleotide sequences of five domains of the CSDaV genomic RNA, including those encoding for the methyltransferase, the multi-domain region (MDR), the helicase, the RNA-dependent RNA polymerase and the coat protein, showed that the MDR coding region was the most diverse region assessed here, and a possible association between this region and virus adaption to different host or plant tissues is considered. Overall, the nucleotide diversity () was low for CSDaV isolates, but the phylogenetic analyses revealed the predominance of two main groups, one of which showed a higher association with CSD-symptomatic plants. Isolates obtained from CSD-symptomatic plants, compared to those obtained from asymptomatic plants, showed higher nucleotide diversity, nonsynonymous and synonymous substitution rates and number of amino acid changes on the coding regions located closer to the 5' end region of the genomic RNA. This work provides new insights into the genetic diversity of the CSDaV, giving support for further epidemiological studies.
Keywords: citrus sudden death; CSDaV; plant virus; Marafivirus; diversity